Applications of toxin-antitoxin systems in synthetic biology - Jianzhong Lin; Yunxue Guo; Jianyun Yao; Kaihao Tang; Xiaoxue Wang (Engineering Microbiology, 2023)
Toxin-antitoxin (TA) systems are ubiquitous in bacteria and archaea. Most are composed of two neighboring genetic elements, a stable toxin capable of inhibiting crucial cellular processes, including replication, transcription, translation, cell division and membrane integrity, and an unstable antitoxin to counteract the toxicity of the toxin. Many new discoveries regarding the biochemical properties of the toxin and antitoxin components have been made since the first TA system was reported nearly four decades ago. The physiological functions of TA systems have been hotly debated in recent decades, and it is now increasingly clear that TA systems are important immune systems in prokaryotes. In addition to being involved in biofilm formation and persister cell formation, these modules are antiphage defense systems and provide host defenses against various phage infections via abortive infection. In this review, we explore the potential applications of TA systems based on the recent progress made in elucidating TA functions. We first describe the most recent classification of TA systems and then introduce the biochemical functions of toxins and antitoxins, respectively. Finally, we primarily focus on and devote considerable space to the application of TA complexes in synthetic biology.